GAMBARAN KLINIKOPATOLOGIK PENYAKIT PROSTAT DI RSUP SANGLAH DENPASAR TAHUN 2018-2020 - Astuti, Ida Ayu Jelantik; Winarti, Ni Wayan; Sriwidyani, Ni Putu; Dewi, I Gusti Ayu Sri Mahendra (Universitas Udayana, 2023)
Prostate disease is one of the diseases with a high incidence among elderly men. . In establishing the diagnosis of prostate disease, histopathological and laboratory examinations are vital. These histopathological results can be grouped into 3, namely benign lesions, PIN, and carcinoma. This study aims to determine the clinicopathological description of prostate diseases at Sanglah Hospital Denpasar from 2018-2020. The cross-sectional research was conducted using the descriptive and analytic method. Samples were selected based on several inclusion and exclusion criteria. Data were analyzed using SPSS version 26 to obtain a general clinicopathological picture based on age, histopathological diagnosis, the relationship between age and histopathological, diagnosis, PSA level, and the relationship between PSA level with histopathological diagnosis, and grade group carcinoma. The results showed that the prostate disease with the most patients at Sanglah Hospital Denpasar from 2018-2020 occurred between the age of 70-79 years by 39,0% with the dominant histopathological diagnosis being benign prostate 240 (74,3%), followed by PIN 27 (8,4%), and carcinoma 56 (17,3%). There was no relationship found between age, mean age and histopathological diagnosis with p=0,881 and p=0,119. The highest PSA level was > 20ng/mL. It was found that the PSA level was significantly associated with histopathological diagnoses with a value of p=0,000. The most prevalent grade group characteristic was grade group 5 with 36 (64,3%). Keywords: Prostate Disease, Clinicopathologic, PSA Level